Impact of welan gum stabilizer on the dispersing performance of polycarboxylate superplasticizers. (April 2016) - Üzer, E.; Plank, J.
Abstract: Welan gum, a microbial biopolymer produced via fermentation, represents a common stabilizer (VMA) for highly dispersed concretes such as e.g. self-compacting concrete (SCC). Here, interaction between welan gum and two methacrylate ester-based polycarboxylate (PCE) superplasticizers was studied. It was found that the stabilizing effect of welan gum solely derives from its strong viscosifying effect on the aqueous phase of concrete ( i.e. cement pore solution). The dispersing effectiveness of PCE is negatively influenced by this increased viscosity. A mechanistic study revealed that the stabilizer does not adsorb on cement and that it does not reduce adsorption of PCE. Thus, no competitive adsorption between the two admixtures occurs. This behavior differentiates welan gum from copolymerized VMAs based on AMPS® which adsorb on cement and can perturb PCE adsorption. When formulating SCC with welan gum as stabilizer, its dosage should be kept as low as possible to preserve the fluidity provided by PCE.